Creative industries and the creative economy of the West of Ireland: evidence of sustainable change?. Issue 1 (2nd January 2018) - Collins, Patrick; Mahon, Marie; Murtagh, Aisling
ABSTRACT: Our goal here is to consider how the rise of the creative economy in the west of Ireland can be situated in broader trends of industrial and economic change. This work is based on a number of EU funded projects (Creative Edge; Creative Momentum) that have sought to prove the nature and extent of the creative economy in Europe's most peripheral regions. Here we consider the key traits of a burgeoning economy and question how it fits into (results from and indeed inspires) the wider context of global economic change. We explore patterns of consuming, making, creating, and sharing and consider how they reside in the creative economy. We situate the performance of creative industries in broader trends in cultural consumption and seek to highlight now their relationship of with their place and their unique approach to doing business could highlight a sustainable development path for peripheral regions in Europe.